Anxiety and inhibition of panic attacks within translational and prospective research contexts Ansiedade e inibição de ataques de pânico no contexto das pesquisas translacionais e prospectivas - Ruan Cabral; Antonio Egídio Nardi (Trends in Psychiatry and Psychotherapy, 2012)
Basic research involving animal models is an important tool to improve our understanding of clinical conditions related with anxiety and panic attacks. In fact, animal models have been used to study several paradigms on analogous and homologous elements of human anxiety phenomena. However, the direct transposition (translation) to clinical practice of the results obtained with animal models may be restricted by the different constructs used to describe and explain empirical evidence of anxiety phenomena among humans. We aimed to analyze whether theoretical assumptions on the potential inhibitory effects of anxiety on panic could be observed among humans in prospective studies designed to analyze the relationship between anxiety and panic. A systematic literature review including papers published in English language between 1997 and 2011 was undertaken on the MEDLINE database. The search yielded a total of 257 articles, of which 11 were included in the review. In three studies, the global dimension of the anxiety sensitivity construct worked as a facilitator of panic attacks. Six studies showed a positive correlation between the AS-Physical Concerns subfactor and the occurrence of panic attacks, whereas two studies found a greater effect of the AS-Mental Incapacitation Concerns subfactor on panic. There was no evidence that anxiety might act as an inhibitor of panic attacks in humans, and there were no conclusive findings on the possibility that any anxiety construct could contribute toward inhibiting panic attacks. In sum, there seems to be a need for refining descriptions of anxious phenomena addressed both in basic preclinical research and in prospective-longitudinal studies involving humans. As pesquisas básicas elaboradas com modelos animais são importantes ferramentas para melhorar a compreensão de condições clínicas relacionadas a ansiedade e ataques de pânico. De fato, modelos animais tem servido de base para vários paradigmas sobre elementos análogos e homólogos aos fenômenos ansiosos humanos. No entanto, a transposição (translação) direta dos resultados dessas pesquisas para a prática clínica pode ser limitada pelos diferentes construtos usados para descrever e explicar as evidências empíricas de fenômenos ansiosos em humanos. Este artigo buscou analisar se proposições teóricas sobre o potencial efeito inibitório da ansiedade sobre ataques de pânico poderiam ser observadas em estudos prospectivos envolvendo humanos e desenhados para analisar a relação entre ansiedade e pânico. Uma revisão sistemática da literatura incluindo artigos publicados em língua inglesa entre 1997 e 2011 foi realizada na base de dados MEDLINE. Foram identificados 257 artigos, dos quais 11 foram incluídos na revisão. Em três pesquisas, a dimensão geral do construto anxiety sensitivity atuou como facilitador de ataques de pânico. Seis pesquisas apresentaram correlação positiva entre o subfator AS-Physical Concerns e a ocorrência de ataques de pânico, e duas apontaram para um maior efeito de favorecimento do pânico pelo subfator AS-Mental Incapacitation Concerns. Não foi possível observar se de fato a ansiedade pode agir como um agente inibidor de ataques de pânico em humanos, e os artigos analisados não ofereceram resultados conclusivos sobre a possibilidade de algum construto sobre ansiedade contribuir para a inibição de ataques de pânico. Em suma, parece evidente a necessidade de um refinamento das descrições sobre fenômenos ansiosos abordados tanto em pesquisas básicas pré-clínicas quanto em estudos prospectivos envolvendo humanos.